Front cover: Functional Effects of the Buckwheat Iminosugar d‐Fagomine on Rats with Diet‐Induced Prediabetes. Issue 16 (24th August 2018) - Ramos‐Romero, Sara; Hereu, Mercè; Atienza, Lidia; Casas, Josefina; Taltavull, Núria; Romeu, Marta; Amézqueta, Susana; Dasilva, Gabriel; Medina, Isabel; Torres, Josep L.
Abstract : Mol. Nutr. Food Res. 2018, 62, 1800373 DOI:10.1002/mnfr.201800373 d ‐Fagomine, an iminosugar found in buckwheat, counteracts the weight gain and elevated blood glucose levels induced by an excessive intake of fat. In article number1800373, Sara Ramos‐Romero and colleagues observe thatd ‐fagomine reduces fat‐related low‐grade systemic inflammation, and partially compensates the changes in gut enterobacteria putatively associated with it. This provides a possible explanation for its effects on type 2 diabetes risk factors. Cover credit: M. Eugenio Vázque.